Peripheral Intravenous Catheter Insertion Competence and Confidence in Medical/Surgical Nurses. Issue 6 (November 2022) - Jacobs, Lisa
Abstract : The objective of this study was to implement an evidence-based practice project to improve peripheral intravenous catheter (PIVC) insertion confidence and competence and to improve first-attempt success. The researcher used a blended online learning module and live simulation to increase PIVC insertion confidence and competence. Internal application of a blended curriculum model improved the first-attempt PIVC insertion success of nurses. A validated confidence assessment was completed by participants (n = 38) preintervention, immediately postintervention, and 30 days postintervention. A Mann-Whitney U test determined that nurses' confidence was significantly higher immediately following the intervention compared with preintervention ( P = .003), and the increase was sustained 30 days after the intervention ( P < .001). While placing a PIVC in simulation, the observer measured competence using a validated tool verifying 28 steps required, with a 76% success rate for all 28 steps. Nurses' self-reported first-attempt PIVC success increased significantly from the preintervention survey to the 30-day postintervention survey ( P = .00004).